1986
DOI: 10.1136/bmj.293.6561.1559
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the preregistration year experience.

Abstract: All 115 graduates qualifying at Liverpool University Medical School in one year were sent a questionnaire in the final week of their preregistration year to assess the experience they had gained.Of the 105 graduates (92%) who replied, 99 (94%) considered the supervision that they had received to be adequate, 89 (85%) received most of their teaching from other junior doctors, and only 47 believed that they had learnt a considerable amount from their consultant colleagues. Half of the doctors received litde or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…A list of tasks was identified from the literature3 – 5 7 12 – 18 and collated under the section headings: 1, communications; 2, on call patient care; 3, routine patient care; 4, laboratory investigations; 5, clinical investigations; 6, practical procedures; and 7, self management. We generated a datasheet of operational definitions, categories of tasks, and space for comments, and we posted this to members of the panel.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…A list of tasks was identified from the literature3 – 5 7 12 – 18 and collated under the section headings: 1, communications; 2, on call patient care; 3, routine patient care; 4, laboratory investigations; 5, clinical investigations; 6, practical procedures; and 7, self management. We generated a datasheet of operational definitions, categories of tasks, and space for comments, and we posted this to members of the panel.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…An exploration of the barriers and difficulties involved in the learning of clinical skills will be made. 22,23,24,25,26,27,28,29,30,31,32,33,34,35 Method…”
Section: Literaturementioning
confidence: 99%
“…Interestingly, a survey of house-officers who had graduated from Liverpool University showed that 85 per cent felt that they had received most of their training from other junior medical staff [67].…”
Section: Proposed Solutionsmentioning
confidence: 99%